1999
DOI: 10.1038/20452
|View full text |Cite
|
Sign up to set email alerts
|

In vivo cell sorting in complementary segmental domains mediated by Eph receptors and ephrins

Abstract: The restriction of intermingling between specific cell populations is crucial for the maintenance of organized patterns during development. A striking example is the restriction of cell mixing between segments in the insect epidermis and the vertebrate hindbrain that may enable each segment to maintain a distinct identity. In the hindbrain, this is a result of different adhesive properties of odd- and even-numbered segments (rhombomeres), but an adhesion molecule with alternating segmental expression has not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
307
2
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 403 publications
(320 citation statements)
references
References 26 publications
(18 reference statements)
7
307
2
1
Order By: Relevance
“…If the elevated Myosin II at the D-V boundary actually decreased cell adhesion, then it would create a stripe of deadhesion at the boundary. A stripe of de-adhesion could create an effective compartment boundary fence, as has been discussed previously in the context of Notch function in D-V compartmentalization, and Eph-ephrin signaling in vertebrate hindbrain compartmentalization (Xu et al, 1999;Mellitzer et al, 2000;Irvine and Rauskolb, 2001). …”
Section: Discussionmentioning
confidence: 96%
“…If the elevated Myosin II at the D-V boundary actually decreased cell adhesion, then it would create a stripe of deadhesion at the boundary. A stripe of de-adhesion could create an effective compartment boundary fence, as has been discussed previously in the context of Notch function in D-V compartmentalization, and Eph-ephrin signaling in vertebrate hindbrain compartmentalization (Xu et al, 1999;Mellitzer et al, 2000;Irvine and Rauskolb, 2001). …”
Section: Discussionmentioning
confidence: 96%
“…The hindbrain region is further partitioned into seven or eight compartments called rhombomeres. Several studies have demonstrated that rhombomeres represent polyclonal compartments (reviewed in Lumsden, 1990) that are distinguished from each other by limited cell movements (Fraser et al, 1990;Birgbauer and Fraser, 1994), differential cell adhesion (Guthrie and Lumsden, 1991;Wizenmann and Lumsden, 1997), differential cell repulsion (Xu et al, 1995(Xu et al, , 1999Cooke et al, 2001;reviewed in Xu et al, 2000;Cooke and Moens, 2002), and compartment-specific expression of homeobox genes (reviewed in Wilkinson and Krumlauf, 1990;Lumsden and Krumlauf, 1996). Each rhombomere contains a characteristic, segmentally reiterated set of neurons, including motor neurons and reticulospinal interneurons (Kimmel et al, 1985;Metcalfe et al, 1986;Lumsden and Keynes, 1989;Clarke and Lumsden, 1993;reviewed in Glover, 2001).…”
Section: The Developing Hindbrainmentioning
confidence: 99%
“…In the zebrafish (vertebrate) hindbrain, ephrin-Eph repulsive interactions play essential roles in generating rhombomere boundaries (Xu et al, 1995(Xu et al, , 1999Cooke et al, 2001;reviewed in Xu et al, 2000;Cooke and Moens, 2002). However, neither the receptors nor the ligands are specifically expressed in the floor plate or BMNs, discounting a role for these molecules in the repulsive guidance away from the floor plate.…”
Section: Ephrinsmentioning
confidence: 99%
“…More recently, Xu et al (1999) showed that cells ectopically expressing ephrin-B2 sort out of r3 and r5 in mosaic embryos. This behavior is independent of retrograde signalling by the ligand-expressing cells, demonstrating that activation of Eph signalling in neighboring cells is sufficient to expel ligand-expressing cells from Eph-expressing rhombomeres in a nonautonomous manner.…”
Section: Repulsive Interactions Between Ephs and Ephrins Mediate Cellmentioning
confidence: 99%